2011
DOI: 10.1504/ijtamm.2011.041174
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic studies of nanohardness size effects

Abstract: Atomistic simulations of nanoindentations with spherical and Berkovich indenters were carried out to study the effects of size on nanohardness. For spherical indenters with the radii ranging from 10 Å to 50 Å, it was found that nanohardness was inversely proportional to the indenter radius. For Berkovich indenters, it was found that nanohardness roughly followed a trend that was inversely proportional to the indentation depth. It was concluded that the indentation size effect at the atomistic scale might follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Many studies have adopted atomistic simulations to probe and understand detailed deformation process and the possible impact factors involved in nanoindentation. For example, Chan et al [10] studied the size effects of indenter nanohardness using atomistic simulations, and found that nanohardness was inversely proportional to the indenter radius. Imran et al [11] studied the influence from the indenter velocity and size of the indenter using molecular dynamics (MD) simulations in Ni single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have adopted atomistic simulations to probe and understand detailed deformation process and the possible impact factors involved in nanoindentation. For example, Chan et al [10] studied the size effects of indenter nanohardness using atomistic simulations, and found that nanohardness was inversely proportional to the indenter radius. Imran et al [11] studied the influence from the indenter velocity and size of the indenter using molecular dynamics (MD) simulations in Ni single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Atomistic modeling has been used to address a wide variety of deformation processes in solids recently (Chen et al 2008, Chan et al 2011, Lai and Chen 2013, Chen and Lee 2010, Jeong et al 2011, Shen 2013, Teng et al 2011, Wang et al 2013, Zhao and Aluru 2008. The advantage of fully atomistic modeling is its capability to provide desirable resolution that accounts for highly inhomogeneous deformations caused by lattice defects in materials.…”
Section: Introductionmentioning
confidence: 99%
“…With recent advances in computing power, researchers have adopted atomistic simulations to probe and understand detailed deformation processes and the mechanisms involved in nanoindentation (Lilleodden et al 2003, Lee et al 2005, Chen et al 2008, Chan et al 2011. Lilleodden et al (2003) carried out an atomistic study of Au nanoindentation and reported the Corresponding author, Professor, E-mail: dchen@ntu.edu.tw elastic anisotropy of Au metal.…”
Section: Introductionmentioning
confidence: 99%
“…For both samples, the mean contact pressure varied significantly during the early stages of indentation but reached a steady value soon after the first apparent load drop. Chan et al (2011) studied the size effects of nanoindentation using atomistic simulations. For spherical indenters with radii ranging from 10 to 50 Å , it was found that nanohardness was inversely proportional to the indenter radius.…”
Section: Introductionmentioning
confidence: 99%